Nowy model kształcenia ratowników medycznych w Polsce w świetle aktualnych regulacji prawnych = The new model of education of medical rescuers in Poland in light of current regulations - Marcin Mikos; Grzegorz Juszczyk; Aleksandra Czerw; Robert Gałązkowski (Kazimierz Wielki University, 2015)
Mikos Marcin, Juszczyk Grzegorz, Czerw Aleksandra, Gałązkowski Robert. Nowy model kształcenia ratowników medycznych w Polsce w świetle aktualnych regulacji prawnych = The new model of education of medical rescuers in Poland in light of current regulations. Journal of Education, Health and Sport. 2015;5(12):110-117. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35190 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A110-117 http://pbn.nauka.gov.pl/works/678366 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 25.11.2015. Accepted: 10.12.2015.     Nowy model kształcenia ratowników medycznych w Polsce w świetle aktualnych regulacji prawnych The new model of education of medical rescuers in Poland in light of current regulations     Marcin Mikos1, Grzegorz Juszczyk2, Aleksandra Czerw2, Robert Gałązkowski3   (1)   Polskie Towarzystwo Prawa Medycznego (2)   Zakład Zdrowia Publicznego, Warszawski Uniwersytet Medyczny (3)   Zakład Ratownictwa Medycznego,  Warszawski Uniwersytet Medyczny   Słowa kluczowe: kształcenie, ratownik medyczny. Keywords: education, medical rescuer.   Streszczenie W przepisach prawach zaszły w ostatnim czasie zmiany, które całkowicie zmieniają model kształcenia ratowników medycznych w Polsce. Do głównych zmian należą wymóg realizacji co najmniej 2455 godzin kształcenia na studiach pierwszego stopnia i konieczność uzyskania co najmniej 80 punktów ECTS, konieczność odbycia 6 miesięcznej praktyki zawodowej, a także obowiązek pozytywnego złożenia Państwowego Egzaminu z Ratownictwa Medycznego. Brak jest  przeszkód prawnych do odbywania przez ratowników medycznych studiów drugiego stopnia i uzyskiwania tytułu zawodowego magistra.   Abstract The provisions of the laws have been recently revised in a way that substantially change the model of training of paramedics in Poland. The major changes include: the requirement to implement at least 2455 hours of education at the undergraduate level and the need to obtain at least 80 ECTS credits, the necessity of the 6-month professional apprentice, and  positive pass of the National Medical Emergency Exam. Therefore there are legal obstacles to open  second degree studies for paramedics, allowing them obtaining a master's degree.